(untitled) - Ceallaigh, S. Ó (London, 2011)
This collection resembles scraps from a diary or an honest C.V. But it doesn't tell the full story. It is one person's view of the world at a given time; many views at many times concerning Sex & Violence, War & Peace, Religion & Politics, Men, Women & Children, Drink & Drugs, Sanity/Insanity. Indeed, "Life is the funniest thing I've experienced so far."We are all capable of being extremely childish and extremely serious, but the one thing we want to do is to communicate with another human being, and we are willing to risk it. This collection may be described as apophatic (in the negative): not suitable for children, not suitable for persons of a sensitive disposition, not politically correct. Integrity and discretion are expected on the part of poets, but may not be possible...
Keywords: Poetry collection,Sưu tập thơ